2015
DOI: 10.1002/mop.29421
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐wideband U‐shape open‐slot antenna for the lte metal‐framed tablet computer

Abstract: The open‐slot antenna is very suitable for applications in the metal‐framed tablet device, such as the tablet computer, to achieve a low profile with wideband or multiband operation. This article presents a U‐shape open‐slot (U‐slot) antenna with a low profile of 7 mm to the top edge of the metal‐framed tablet computer for the LTE operation. The U‐slot has a simple structure of length 70 mm and the two slot openings thereof are disposed at the metal frame. The U‐slot antenna is fed using an end‐shorted 50‐Ω mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Slot antennas are widely adopted as an alternative for mobile antenna designs [10][11][12][13][14][15][16]. Two folded slot antennas were introduced in [10,11] to cover dual bands.…”
Section: Introductionmentioning
confidence: 99%
“…Slot antennas are widely adopted as an alternative for mobile antenna designs [10][11][12][13][14][15][16]. Two folded slot antennas were introduced in [10,11] to cover dual bands.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the open‐slot antenna is promising to be applied in the metal‐framed slim mobile device such as the smartphone and tablet computer for the LTE (long‐term evolution) operation . The metal frame around the slim mobile device can increase the robustness thereof and can also be used as an extended ground portion of the open‐slot antenna disposed in the system ground plane therein.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is noted that many reported LTE open‐slot antennas disposed along one edge of the mobile device can provide one LTE low band (LB) below 1 GHz and one LTE middle/high band (M/HB, 1710–2690 MHz) only. For the metal‐framed smartphone application, two such open‐slot antennas can be disposed at two (top and bottom) short edges thereof to be applied for the 2 × 2 LTE MIMO (multi‐input multi‐output) operation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to apply to the slot antenna because the characteristics of the impedance are different from those of the IFA. A slot antenna with open end is proposed to increase the antenna bandwidth . However, in actual practice, this requires cutting the metal frame, which places constraints on the design options.…”
Section: Introductionmentioning
confidence: 99%